An Analysis of Application of Project-Based Learning to Improve Writing Skills of Mechanical Engineering Students - Umi Anis Roisatin; Moh Thamrin; Noverita Wahyuningsih (Bulletin of Pedagogical Research, 2022)
Based on previous research, students’ writing skills are considered too low especially in conveying ideas, choosing vocabularies, and arranging the vocabularies to build sentences. And then arrange the sentences as a complete paragraph. This research is motivated by the students’ low writing skills which significantly impacting the students’ skills to write research abstract, job applications, class presentations, and presentations for thesis defense in front of the board examiners. It is a descriptive-qualitative research that conducted with the research subject of 2nd semester students of Department Mechanical Engineering State Polytechnic of Malang. The method used for the research is writing some paragraphs using different tenses and then analyzing the basic writing mistakes of the written paragraphs. After that, students’ writen a set of instruction consisted of six or more sentences that indicate a process. The results are satisfying because the students' writing skills are increased compared to before conducting this research using project-based learning, even though there are still mistakes both in terms of language and from a grammatical point of view. Keyword :Project Based Learning, Writing Skill, Improving Writing